Resistance to US State Terrorism in the 21st Century in Urdu Qit’a - Wadood, Tariq; Munir Bukhari, Badshah (sourcecoder, 2022)
This study analyses the Urdu literature Qit’a (قطعہ) regarding the resistance towards the state terrorism of the United States. The study aimed to explore the various hegemonic techniques of the United States to control the Muslim countries (Iraq, Afghanistan, and Pakistan) through the imposition of New World Order under the shield of war on terror. The belligerent voice of ten poets has been the scope of the study. The analysis shows the poets expressed their utter disapproval, and anger and protested against the state terrorism of the United States. They express their ideas in an ironic and satiric manner. This study recommended studying the other genres of the poets to lay bare the state terrorism for the vested interests of the United States.